Capital Intensity as a Moderator of the Relationship Between Profitability, Leverage, and Tax Aggressiveness: Evidence from Indonesia's Food and Beverage Sector - Amin, Rahmahdani; Junaid, Asriani; Nurfadila, N. (Manunggal Halim Jaya, 2025)
This study aims to determine and analyze the effect of profitability and leverage on tax aggressiveness, moderated by capital intensity. The population in this study was manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2021-2023, using a purposive sampling technique. The secondary data used in this study were accessed through www.idx.co.id. Data obtained in this study were from 71 companies that met the criteria. The analysis results show that profitability negatively and significantly affects tax aggressiveness. Meanwhile, leverage has a positive and significant effect on tax aggressiveness. The moderating variable, capital intensity, moderates the relationship between profitability and tax aggressiveness in a negative and significant direction, and the moderating variable, capital intensity, moderates the relationship between leverage and tax aggressiveness in a positive and significant direction.